Body height differentiation by season of birth: Girls from Cracow, Poland - Puch, Elżbieta Alicja; Krenz-Niedbała, Marta; Chrzanowska, Maria (Anthropological Review, 2008)
Published studies world wide demonstrate that measures of human development and health status vary depending on the month of birth but these patterns are not always consistent and sometimes even conflict. Direct factors related to the birth season that may significantly differentiate morphological and functional traits and mechanisms causing these relations have not been found so far. On the basis of cross-sectional material, gathered in the years 1983 and 2000 by the Department of Anthropology of the Academy of Physical Education in Cracow, two main hypotheses have been verified: (1) average body height differences by month of birth are statistically insignificant, (2) the magnitude of these differences does not change with time. Metric data of 4672 girls aged 5-18 years, born in 1965-1978 and 1982-1995, were used. The total sample was also subdivided into prepubertal (5-9 years) and adolescent (10-18 years) groups. The age of the individuals was calculated to the nearest day and the procedure of standardization on the interpolated values of regional norms was applied. A highly significant relationship between the birth month and average values of height was revealed in preadolescent girls. The results obtained for the entire material proved insignificant. The patterns of the month-of-birth effect on body height for girls born in 60./70. and 80./90. show high similarity, though the effect seems weaker in the latter sample. Winter proved to be the most favorable birth season for later body height.